Application of GSTARMA Spatial-Temporal Model for Inflation Analysis in South Sulawesi Province - Sari, Dede Ratna; Widiarti; Nurvazly, Dina Eka; Usman, Mustofa; Loves, Luvita (Integra: Journal of Integrated Mathematics and Computer Science, 2024)
The Generalized Space-Time Autoregressive Moving Average (GSTARMA) model is a development of the time series model that can capture both spatial and temporal dynamics simultaneously. This study uses the GSTARMA model to analyze inflation data in five cities in South Sulawesi Province from January 2017 to October 2024. The GSTARMA model obtained is GSTARMA (1,0,1) with a cross-correlation normalization spatial weight matrix. The results of the analysis indicate a spatial influence between locations and temporal relationships in the inflation data.